Winners and Losers: Gerrymandering and the Wisconsin Supreme Court Case - Dahleh, Jumana; Eckert, Sam; Edelman, Chet; Kerwin, Katherine (My University, 2017)
The objective of this research is to examine the validity of the gerrymandering claims being levied against the current Wisconsin State Assembly map in the Gill v Whitford Supreme Court case. To test these claims we examined the first elections following the 1991, 2001, and 2011 decennial assembly redistricting. More specifically, we compared the 1992 and 2002 elections with the controversial 2012 election. Utilizing the efficiency gap, a metric that measures gerrymandering through calculating the so-called “wasted vote,” we observed the level of gerrymandering in each year to determine whether 2012 stood out as an anomaly. Furthermore, we also tested the counterargument that partisan migration, as measured by district level changes in vote share, is the root cause of Wisconsin’s electoral upheaval. In our analysis we found that Wisconsin’s 2012 assembly election did in fact have an efficiency gap calculation substantially higher than previous elections, indicating gerrymandering was likely in play. Furthermore, we found that partisan migration could not be sufficiently correlated with changes in the efficiency gap, therefore negating the partisan migration theory.
Includes Figures, Maps, Appendices and Bibliography.
Keywords: Gerrymandering; Wisconsin; Gill v Whitford